2004
DOI: 10.1038/sj.bjc.6602042
|View full text |Cite
|
Sign up to set email alerts
|

UGT1A1 gene variations and irinotecan treatment in patients with metastatic colorectal cancer

Abstract: SN-38 is the active metabolite of irinotecan and it is metabolised through conjugation by uridine diphosphate glucuronosyl transferase (UGT1A1). The major toxicity of irinotecan therapy is diarrhoea, which has been related to the enzymatic activity of UGT1A1. We examined the influence of the UGT1A1 gene promoter polymorphism in the toxicity profile, in the response rate and in the overall survival (OS) in 95 patients with metastatic colorectal cancer treated with an irinotecan-containing chemotherapy. Genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
176
2
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(193 citation statements)
references
References 19 publications
10
176
2
4
Order By: Relevance
“…Interestingly, diarrhea did not correlate with UGT1A1 genotype in this study population, perhaps owing to reduced enterohepatic recycling of SN-38G and a lower intestinal exposure to SN-38. However, Marcuello et al (2004) contradicted these findings in that the UGT1A1*28 genotype associated with diarrhea but not neutropenia in 95 patients with metastatic CRC. Additionally, as with irinotecan pharmacokinetics, UGT1A7 and 1A9 have been reported to predict irinotecan toxicity (Carlini et al, 2005).…”
Section: Ugt1a1 Polymorphisms and Cancer: Genotype-phenotype Correlationcontrasting
confidence: 42%
“…Interestingly, diarrhea did not correlate with UGT1A1 genotype in this study population, perhaps owing to reduced enterohepatic recycling of SN-38G and a lower intestinal exposure to SN-38. However, Marcuello et al (2004) contradicted these findings in that the UGT1A1*28 genotype associated with diarrhea but not neutropenia in 95 patients with metastatic CRC. Additionally, as with irinotecan pharmacokinetics, UGT1A7 and 1A9 have been reported to predict irinotecan toxicity (Carlini et al, 2005).…”
Section: Ugt1a1 Polymorphisms and Cancer: Genotype-phenotype Correlationcontrasting
confidence: 42%
“…Carriers of the UGT1A1*28 7/7 homozygous genotype showed higher risk for suffering Grade III/IV neutropenia than UGT1A1*28 6/6 carriers. The association the UGT1A1*28 variant and side-effects from irinotecan-based chemotherapy has been described in previous studies [20][21][22][23] and according to present and recently reported data, it seems that the side-effect that is more frequently associated with UGT1A1*28 status is myelotoxicity. 23,[40][41][42][43] Toffoli et al 23 also found a favorable association between UGT1A1*28 7/7 better response rate and survival.…”
Section: Folfiri Pharmacogenetics In Colorectal Cancermentioning
confidence: 83%
“…4 UGT1A1*28 has been correlated with increased risk of severe toxicity after irinotecan chemotherapy, [20][21][22][23] and it is unclear whether this variant may also influence treatment outcomes. 23 In experimental models, SN-38 showed induction of DNA damages, which require the activation of the nucleotideexcision repair (NER), the base-excision repair (BER) and the homologous recombination repair (HR) pathways.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The clinical application of the genetic test for the UGT1A1*28 allele before irinotecan therapy has been in practice in the United States since 2005, based on a cumulative evidence supporting the significant association of this variant with severe irinotecan toxicity. 20,[22][23][24][25] The five most associated SNPs included rs4148323 (G4A, UGT1A1*6). Homozygotes of the UGT1A1*6 allele showed significantly high values in serum total bilirubin levels, supporting the evidence from earlier studies.…”
Section: Discussionmentioning
confidence: 99%